Determinants of rice farmer's access to credit in niger state, nigeria (2011)
"The performance of the agricultural sector has been relatively poor considering the attitude of existing financial institutions to the support of the sector. Informal credit supply is limited while formal credit supply is often inaccessible to smallholder farmers. Therefore, borrower's characteristics that determine access to formal and informal sources of credit were examined. Data collected by the Africa Rice Centre from Niger State in 2009 were used. Multi-stage sampling technique was used to obtain a sample of 373 out of 470 rice farmers from whom information was collected. Descriptive statistics and multinomial logit model were then used to analyse the data. Results revealed that agricultural credit programmes and village residents in the formal and informal credit sectors respectively were the accessible sources of credit. The results also revealed that access to formal credit was significantly increased by experience in rice farming, expenses on fertilizer input and rice income while access to informal credit was significantly increased by gender, duration of village residency, experience in rice farming and expenses on fertilizer input. It is recommended that a suitable credit support programme for access to formal credit should be introduced. "